Primitive Neuroectodermal Tumor of the Cervix Uteri - Zineb Benbrahim; Christine Haie-Meder; Pierre Duvillard; Omar El Mesbahi; Axel Le Cesne; Patricia Pautier (International Journal of Hematology-Oncology and Stem Cell Research, 2012)
Ewing’s sarcoma is a round cell malignancy of bone and soft tissue that occurs predominately in adolescents and young adults.It is an uncommon malignancy, but is recognized as the second most prevalent primary bone tumor worldwide. Extraosseous Ewing’s sarcoma is extremely rare and can affect the skin, soft tissues, or viscera. Prognostic and therapeutic features of Ewing’s extraosseous tumors are similar to those of Ewing’s sarcoma. A primary Ewing’s sarcoma arising from the cervix is highly rare. Most of these patients presented with abnormal vaginal bleeding. We report a case of extraskeletal Ewing’s sarcoma arising in the cervix in a 25-year-old woman.